A Meta-analysis of Intravenous Iron Therapy for Patients With Iron Deficiency and Heart Failure - Osman, Mohammed; Syed, Moinuddin; Balla, Sudarshan; Kheiri, Babikir; Faisaluddin, Mohammed; Bianco, Christopher (The American journal of cardiology, 2021)
Early randomized clinical trials (RCTs)1–4 evaluating the efficacy of intravenous iron replacement in heart failure patients with iron deficiency showed promising results in improving objective clinical outcomes, including heart failure hospitalizations and cardiovascular mortality. The 2017 ACC/AHA/HFSA focused guideline update provides a IIb recommendation for intravenous iron repletion in NYHA class II and III heart failure patients and iron deficiency to improve functional status and quality of life.5 Most recently, the results of the AFFIRM-AHF (A Randomized, Double-blind Placebo-Controlled Trial Comparing the Effect of Intravenous Ferric Carboxymaltose on Hospitalisations and Mortality in Iron Deficient Subjects Admitted for Acute Heart Failure) was presented in the American Heart Association Scientific Sessions and has refueled the interest regarding the utility of intravenous iron therapy in patients with heart failure.4 We aimed to pool results from all randomized controlled trials evaluating the efficacy of intravenous iron in improving cardiovascular outcomes in patients with heart failure with reduced ejection fraction (HFrEF). Randomized trials examining the role of oral iron on improving clinical endpoints in heart failure patients have failed to show benefit likely due to poor absorption of oral iron in the setting of chronic inflammatory state associated with heart failure.1–4 In conclusion, in patients with HFrEF and iron deficiency, treatment with intravenous iron therapy has reduced the risk of heart failure hospitalization by almost 30% with no difference in all-cause mortality and cardiovascular mortality compared to standard of care.Disclosures The authors have no conflicts of interest to report.